Subglottic secretion drainage for preventing ventilator-associated pneumonia: an overview of systematic reviews and an updated meta-analysis - Diana P. Pozuelo-Carrascosa; Ángel Herráiz-Adillo; Celia Alvarez-Bueno; Jose Manuel Añón; Vicente Martínez-Vizcaíno; Iván Cavero-Redondo (European Respiratory Review, 2020)
Although several guidelines recommend subglottic secretion drainage as a strategy for prevention of ventilator-associated pneumonia (VAP), its use is not widespread. With the aim to assess the effectiveness of subglottic secretion drainage for preventing VAP and to improve other outcomes such as mortality, duration of mechanical ventilation and length of stay in the intensive care unit (ICU) or hospital, an electronic search of the Cochrane Library, MEDLINE, Web of Science and Embase was undertaken. Nine systematic reviews with meta-analysis (in the overview of reviews) and 20 randomised controlled trials (in the updated meta-analysis) were included. In the overview of reviews, all systematic reviews with meta-analysis included found a positive effect of subglottic secretion drainage in the reduction of incidence of VAP. In the updated meta-analysis, subglottic secretion drainage significantly reduced VAP incidence (risk ratio (RR) 0.56, 95% CI 0.48–0.63; I2=0%, p=0.841) and mortality (RR 0.88, 95% CI 0.80–0.97; I2=0%, p=0.888). This is the first study that has found a decrease of mortality associated with the use of subglottic secretion drainage. In addition, subglottic secretion drainage is an effective measure to reduce VAP incidence, despite not improving the duration of mechanical ventilation and ICU and/or hospital length of stay.